2021
DOI: 10.1038/s41385-020-00358-3
|View full text |Cite
|
Sign up to set email alerts
|

Orally desensitized mast cells form a regulatory network with Treg cells for the control of food allergy

Abstract: Oral immunotherapy (OIT) is an effective approach to controlling food allergy. Although the detailed molecular and cellular mechanisms of OIT are unknown currently, they must be understood to advance the treatment of allergic diseases in general. To elucidate the mechanisms of OIT, especially during the immunological transition from desensitization to allergy regulation, we generated a clinical OIT murine model and used it to examine immunological events of OIT. We found that in mice that completed OIT success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 63 publications
(52 reference statements)
1
28
0
Order By: Relevance
“…Wang et al (2019) reported that TReg cells play a major role in the development of immunosuppressive tumor microenvironment mainly through cytokine signal transductions-a key determinant of immunosuppressive potential and unfavorable clinical outcomes. Inconsistent with these findings, we found that BC patients with a high TReg level had a better prognosis than those with a low TReg level (Takasato et al, 2020). The origin of tumor-infiltrating TReg cells and their association with circulating TReg cells are rarely reported, which will be explained in the follow-up study in our following publications.…”
Section: Discussionsupporting
confidence: 76%
“…Wang et al (2019) reported that TReg cells play a major role in the development of immunosuppressive tumor microenvironment mainly through cytokine signal transductions-a key determinant of immunosuppressive potential and unfavorable clinical outcomes. Inconsistent with these findings, we found that BC patients with a high TReg level had a better prognosis than those with a low TReg level (Takasato et al, 2020). The origin of tumor-infiltrating TReg cells and their association with circulating TReg cells are rarely reported, which will be explained in the follow-up study in our following publications.…”
Section: Discussionsupporting
confidence: 76%
“…There is growing evidence that MCs play an important role in inhibiting allergic reactions and inflammation. It has been found that oral immunotherapy (OIT)-induced desensitized MCs have a robust regulatory function and can cooperate with Tregs to form a regulatory network, which helps control food allergy [ 8 ]. It has been reported that the anti-allergic part of MCs is mainly realized through the production of regulatory cytokines, such as IL-2 and IL-10 [ 8 ].…”
Section: Regulatory-type Actions Of Mcs In Allergy and Inflammationmentioning
confidence: 99%
“…It has been found that oral immunotherapy (OIT)-induced desensitized MCs have a robust regulatory function and can cooperate with Tregs to form a regulatory network, which helps control food allergy [ 8 ]. It has been reported that the anti-allergic part of MCs is mainly realized through the production of regulatory cytokines, such as IL-2 and IL-10 [ 8 ]. Several studies have found that the inhibition of the immune responses in the skin, intestines and bladder by MCs depends on IL-10 [ 22 ].…”
Section: Regulatory-type Actions Of Mcs In Allergy and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations